DEVELOPMENT OF IMPORT-SUBSTITUTING TECHNOLOGIES FOR BUILDING MATERIAL PRODUCTION - N. I. Berezovsky; N. P. Voronova; S. M. Gribkova; B. V. Lesun (Наука и техника)
The paper presents results of investigations on rational usage of mineral resources. In particular, it has shown the possibility to increase a period of raw material serviceability and its application for production of building products depending on chemical and mineralogical composition of the waste. Analysis of the executed investigations shows that import substitution of anthracite, lignite and black coal for local fuels (milled peat and its sub-standard product) is possible in the production technology of porous building materials.A mathematical model for drying process has been developed in the paper. Technology for thermal performance of a sintering machine with calculation of its length at the given pallet speed has been proposed on the basis of the developed model. Once-through circulation of flue gases and heated materials is the main specific feature of belt sintering machines being used in production. In such a case the whole drying process can be divided into two periods: a period of constant drying rate and a period of falling drying rate. Calculations have shown that the drying rate depends on moisture content but it does not depend on heat exchange Bio-criteria, however, heating rate is a function of temperature and Biq. A mechanism of moisture transfer using various drying methods is the same as in an environment with constant temperature and so in an environment with variable temperature. Application of the mathematical model provides the possibility to save significantly power resources expended for drying process.The paper gives description of methodology for calculation of technologically important optimum parameters for sintering processes of agglomeration while using milled peat.